Bangladesh : the price of freedom - Rai, Raghu, 1942-; Alam, Shahidul (New Delhi : Niyogi Books, 2013)
In early 1971, when negotiations for an autonomous East Bengal broke down, brutalities against the citizens of erstwhile East Pakistan led to a mass exodus of refugees into India. Despite an international outcry, the assaults and rapes continued. With the intervention of the Indian Armed Forces in December 1971, after nine months of violence and uncertainty and a twelve-day war between India and Pakistan, the independent nation of Bangladesh was born. Ace photographer Ragu Rai documented the plight of the refugees, the action during the war and the jubilant scenes of victory and Independence. His treasure trove of photographs, which for over four decades he thought had been lost, was recently rediscovered. The stories are perhaps not unknown, but have been retold by a master storyteller-the refugee camps, the exodus, the never-ending journey, a whirlwind of poignant, tormented history. And finally, a new nation, a new tomorrow. Bangladesh: The Price of Freedom are never before seen photographs which comprise a significant body of work documenting a turning point in the history of South Asia.
ARC
Keywords: Architecture; Bangladesh -- History -- Revolution, 1971 -- Pictorial works; Bangladesh -- Pictorial works